Strategi Pembelajaran Fikih Berbasis Kitab Turats di Pesantren Modern - Khairul Umam; Saifullah Saifullah; Tarmizi Ninoersy (Jurnal Ilmiah Guru Madrasah, 2025)
Fiqh learning based on classical Islamic texts (kutub al-turāts) remains a distinctive characteristic of Islamic boarding schools in Indonesia; however, at the Aliyah level it still faces challenges such as limited proficiency in classical Arabic, low active learning engagement, and the need for adaptation to modern educational demands. This study aims to describe the fiqh learning strategies based on kitab turats and analyze the challenges encountered in their implementation for second-year Aliyah students at Tgk. Chiek Oemar Diyan Modern Islamic Boarding School and Dayah Insan Qur’ani in Aceh Besar. This research employed a qualitative descriptive method involving fiqh teachers and students as informants, with data collected through observation, interviews, and documentation. The findings indicate that learning strategies involve sorogan, bandongan, and individual mentoring methods supported by pedagogical adaptation to improve contextual comprehension of classical texts. The main challenges include students’ limited Arabic proficiency, a shortage of teachers specializing in classical texts, and limited instructional time. Abstrak Pembelajaran fikih berbasis kitab turats merupakan karakter utama pendidikan pesantren, namun pada tingkat Aliyah masih menghadapi kendala dalam penguasaan bahasa Arab klasik, partisipasi belajar aktif, dan penyesuaian dengan tuntutan pendidikan modern. Penelitian ini bertujuan mendeskripsikan strategi pembelajaran fikih berbasis kitab turats serta menganalisis tantangan dalam implementasinya pada santri kelas 2 Aliyah di Pesantren Modern Tgk. Chiek Oemar Diyan dan Dayah Insan Qur’ani Kabupaten Aceh Besar. Penelitian ini menggunakan metode kualitatif deskriptif dengan informan guru fikih dan santri, melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa strategi pembelajaran yang digunakan meliputi metode sorogan, bandongan, dan bimbingan individual, dengan adaptasi pedagogis untuk meningkatkan pemahaman teks klasik secara kontekstual. Kendala utama meliputi keterbatasan kemampuan bahasa Arab, kurangnya guru ahli kitab klasik, serta alokasi waktu yang terbatas.